PURIFICATION OF PREGNANT SOLUTION RESULTED FROM SPHALERITE CONCENTRATE EXTRACTION USING SULFATE ACID FOR ZINC OXYDE PRODUCTION - Yuhelda Yuhelda; Dessy Amalia; Putri Dewi Novianti; Erlina Yustanti (Puslitbang tekMIRA, 2019)
Purification of pregnant solution from sphalerite concentrate extraction using sulfate acid to produce zinc oxide was meant to prepare zinc oxide production technology utilizing existing internal sphalerite mineral raw material. The pregnant solution used to produce zinc oxide contains 29.84% zinc (Zn), with the biggest impurities iron (Fe) 11.68%. In order to obtain high purity zinc oxide, the pregnant solution should be recovered. It was done through solvent extraction method, in two process steps: extraction and stripping. The extraction was applying ligan bis di2ethylhexyle phosphate acid (D2EHPA) in toluene solvent, through ligan concentrate variation, pH and comparison of aqueous volume with organic volume (VA:Vo) and its excess. Stripping was carried out using sulphate acid through variation of concentration, pH and Vo:VA. To obtain optimum recovery, thus extraction and stripping should be carried out in many steps. The extractions and the strippings were calculated using McCabe Thiele diagram. Furthermore, zinc oxide was resulted from deposition and calcination of pure pregnant solution at temperature 700°C. Purification results show that the best extraction occurred at concentration D2EHPA 1 M, pH 3 and Vo:Va 2:1, through 4 step processes obtained recovery 97.50% with distribution coefficient 77.9; while the best stripping was obtained at H2SO4 concentration 2 M, VO:VA 2:1 through 3 step processes which obtained stripping percent 98.22% with stripping coefficient 1.51. On the other hand, zinc oxide solution resulted from purification was obtained Zn 93.31% in the form of hexagonal crystals (wurtzite).